Regroupment Camps and Shantytowns in Late-Colonial Algeria - Benjamin Claude Brower (L’Année du Maghreb)
This paper examines how the French state responded to the crisis of sovereignty it faced in late-colonial Algeria by confining Algerian civilians in regroupment camps, as well as by the way that it approached people living in the shantytowns of Algiers. It concludes that although different modalities of power distinguished the regroupment camps from the shantytowns, that both sought to neutralize the political agency of Algerians.